2010
DOI: 10.1016/j.micres.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of the exo-β-1,3-glucanase from the mycoparasitic fungus Trichoderma asperellum

Abstract: The regulation of the gene encoding the extracellular exo-beta-1,3-glucanase (tag83) produced by the mycoparasite Trichoderma asperellum was studied. Enzyme activity was detected in all carbon sources, but the highest levels were found when starch and purified cell walls from Rhizoctonia solani were used. These results are supported by the appearance of one strong band with enzyme activity in non-denaturing PAGE. Experiments using RT-PCR showed that exo-beta-1,3-glucanase induction in T. asperellum occurred at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 19 publications
3
37
0
5
Order By: Relevance
“…The cbh1 gene was 100-fold more expressed in the mutant gna1QL in comparison to the TU-6 in 48 hours of culture and decreased drastically after 72 hours (Figure 2). Another gene of great importance in mycoparasitism is gluc83 that encodes to a glucanase [30]. The transcript levelof gluc83 was the same in TU-6 and mutant gna1QL after 48 hours of cultivation, however, the transcript level of gluc83 in the mutant gna1QL decreased by 1.5-fold after 72 hours of cultivation (Figure 2).…”
Section: Gna1 Regulates the Expression Of Cwdes Genes In T Reeseimentioning
confidence: 98%
“…The cbh1 gene was 100-fold more expressed in the mutant gna1QL in comparison to the TU-6 in 48 hours of culture and decreased drastically after 72 hours (Figure 2). Another gene of great importance in mycoparasitism is gluc83 that encodes to a glucanase [30]. The transcript levelof gluc83 was the same in TU-6 and mutant gna1QL after 48 hours of cultivation, however, the transcript level of gluc83 in the mutant gna1QL decreased by 1.5-fold after 72 hours of cultivation (Figure 2).…”
Section: Gna1 Regulates the Expression Of Cwdes Genes In T Reeseimentioning
confidence: 98%
“…This gene was isolated from T. aspererllum and characterized. The expression analysis of this gene was studied using real-time and reverse transcription-polymerase chain reaction (RT-PCR) [42]. Two various kinds of glucanases (β-1,3 and β-1,6 glucanase genes) isolated from T. virens found that these genes secrete cell wall degrading enzyme that helps in the biocontrol activity against R. solani.…”
Section: Interaction Of Genes or Proteins Of Trichoderma Spp With Rmentioning
confidence: 99%
“…i.e., within the columns at P<0.05, MSD: Minimum significant difference at P<0.05 Table 2 : Extracellular enzymes production potency of B. bassiana strains The production of cell wall degrading enzymes is one of the important aspect involved in the control of phytopathogenic fungi. Most of the phytopathogenic fungi possess cell walls that compromises of chitin, as a structural backbone arranged in regularly ordered layers and β-1, 3-glucan as a filling material arranged in an amorphous manner (Marcello et al, 2010). This study showed that all B. bassiana strains could produce β-1, 3-glucanase and chitinase enzyme (Table 2) respectively on 2 , 4 and 6 day, however, the maximum amount th of chitinase was produced on 4 day by all the strains.…”
Section: O N L I N E C O P Ymentioning
confidence: 99%